Un-quaring San Francisco in Milk and Test - Clayton Dillard (European Journal of American Studies)
This article examines San Francisco’s historically diverse queer districts in relation to the homonormativity present in Milk (Gus Van Sant, 2008) and Test (Chris Mason Johnson, 2013) as a means to reclaim the city’s quare spaces. Milk conceals difference through its spatial depiction of an emerging gay civil rights, where not only “gay” but also a coherent social space for queer people comes to be synonymous with whiteness. Accordingly, the largely gay white male population of the Castro District becomes a monolithic emblem of queer history in the city, and restricts access to the queer histories of the Tenderloin and Mission districts, among others. While it is perhaps unsurprising that Milk, a prestige Hollywood film, engages homonormative depictions of queerness, the fact that Test, an American indie, presents San Francisco in a similar manner demonstrates how pernicious this discourse is and that it persists no matter the industrial formation.